ANALYSIS OF TRAINING, COMPETENCY, AND ORGANIZATIONAL CULTURE ON PERSONNEL PERFORMANCE WITH THE MEDIATION OF AFFECTIVE COMMITMENT - Dwi Gastimur Wanto; Retno Kusumatuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to measure the increase in job performance through training, competence, and organizational culture and is mediated by affective commitment. The data collected from 206 personnel from the Semarang Ungaran Police were processed using the Structural Equation Model-Partial Least Square (SEM-PLS) modeling technique. The results of the study show that training, competence, and organizational culture positively and significantly affect affective commitment. Affective commitment, training, and organizational culture variables have a significant positive effect on job performance. Meanwhile, one other variable, namely competence, does not affect job performance. The mediation test results show that affective commitment can mediate the effect of training, competence, and organizational culture on job performance. This research contributes to helping the Ungaran Semarang Police by providing appropriate strategies to improve the job performance of police personnel. This strategy is then expected to boost the job performance of personnel members of the Ungaran Semarang Police. The novelty of this research lies in the fact that it empirically uses a model of the influence of training, competence, and organizational culture on job performance by integrating affective commitment to analyze the increase in job performance of members of the Ungaran Semarang Police personnel. Keywords: Training, competence, organizational culture, affective commitment, job performance